2017
DOI: 10.1021/acs.energyfuels.7b02224
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian Estimation Model for Transient Engine Exhaust Characterization Using Fourier Transform Infrared Spectroscopy

Abstract: Comprehensive emissions models extensively use engine exhaust data from vehicle experiments to represent the relationship between fuel composition and pollutants. However, the predicted emissions from these models often neglect the effects of transients and speed-load history. Fourier transform infrared (FTIR) spectroscopy is a high frequency measurement technique capable of comprehensive speciation. However, due to long residence times of exhaust within a FTIR spectrometer gas cell, FTIR measurements are cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The limitations of FTIR spectroscopy regarding transient analysis are addressed with the implementation of a previously developed UKF, which has been experimentally validated against numerous measurements of compositionally evolving samples. This algorithm and its validation have been thoroughly detailed in previous works and are therefore only briefly explained here. A UKF is an algorithm that couples model predictions with measurements to obtain statistically optimized estimations of the states of a system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of FTIR spectroscopy regarding transient analysis are addressed with the implementation of a previously developed UKF, which has been experimentally validated against numerous measurements of compositionally evolving samples. This algorithm and its validation have been thoroughly detailed in previous works and are therefore only briefly explained here. A UKF is an algorithm that couples model predictions with measurements to obtain statistically optimized estimations of the states of a system.…”
Section: Methodsmentioning
confidence: 99%
“…The model predicts VOC emissions according to the map value that corresponds to the current engine speed and load. To address sample recirculation and spectral IR intensity stationarity issues associated with FTIR measurements of the sample with rapidly evolving composition, a previously developed unscented Kalman filter (UKF) , is employed to filter FTIR measurements. This algorithm utilizes simple models for residence time distribution and sample absorbance evolution to estimate the composition of the sample entering the FTIR gas cell during a measurement period, thereby enabling time-resolved estimates of comprehensive emissions.…”
Section: Introductionmentioning
confidence: 99%
“…A high-level overview of the UKF is presented, followed by a detailed discussion of the state transition and measurement models for the FTIR gas cell system. Details of the UKF and its fundamental equations are omitted for brevity, but interested readers are referred to the following literature. …”
Section: Methodsmentioning
confidence: 99%
“…The residence time issue can be overcome by estimating the composition of sample entering the FTIR gas cell ( Z in in Figure ) during a measurement period according to the evolution of the measured total gas cell composition ( Z cell ). , This method requires a residence time distribution model, which provides a relationship between inlet and total gas cell composition. Previous work has shown that the well-mixed model sufficiently represents this relationship for typical flow rates . While this method improves the overall trend in estimated instantaneous engine exhaust compared to raw measurements, noise from the FTIR measurements greatly exacerbates in inlet composition estimations, resulting in considerable errors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation